Penyusunan Kebutuhan Perangkat E-Banking dengan Pendekatan UI Analysis - Surya Dinata; Martinus Raditia Sigit Surendra (ULTIMA InfoSys, 2014)
This paper propose a method to collect software requirement (Software Requirement Specification – SRS) using user interface analysis on several running and stable system. In this paper we analyzed user interfaces of five internet banking system in Indonesia. The result are list of internet banking features. Then the features are categorized into three category, which are most important, important, and addiontal. Index Terms: Software Requirement Specification (SRS), Use case (UC), Internet banking, Reverse Engineering